Clock, David Sassoon Clock Tower - Ghosh, Ayan (2023)
The David Sassoon clock tower is 67 feet high and has four clocks provided with patent opal glass dials, each measuring four feet in diameter. Unlike many other clock towers in Mumbai, which have stopped functioning, the clocks at the David Sassoon clock tower are all in working condition.